About cataloguing, addressing challenge: cataloguing from textual sign post in Winnebago Spectrum5 to KOHA ILS MARC21: a case study/ Mohd Ariff Shah Muhammad Dzazuli, Haslinda Husaini and Mazwani Ayu Mazlan - Muhammad Dzazuli, Mohd Ariff Shah; Husaini, Haslinda; Mazlan, Mazwani Ayu (Faculty of Information Management, 2022)
The challenges faced by the library in migrating the bibliographic record from the textual signpost definition to proper cataloguing MARC21 format using the open-source library management system, KOHA, are discussed in this case study. The experiences also emphasize the significance of exposing in educating non-library science library staff to enhanced library science information, particularly from a textual signpost catalogue in Winnebago Spectrum to a MARC21 bibliographic format in Koha Integrated Library System It is a member of the German Malaysian Institute (GMI) Library's experienced staff who has no expertise or background in library science. This case study presents the experience on imparting knowledge to the non-library science background staff who used to perform copy cataloging from textual sign post catalogue due to issues faced by the old software itself, to MARC21 bibliographic format containing numerical tags and fields.